Peran Pengawas Ketenagakerjaan dalam Pelaksanaan Sistem Manajemen Keselamatan dan Kesehatan Kerja (SMK3) Sebagai Upaya Meningkatkan Pencegahan Kecelakaan Kerja di Perusahaan Ditinjau dari Peraturan Pemerintah Nomor 50 Tahun 2012 Tentang Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja - Maruhawa, David Nathanael; Karsona, Agus Mulya; Singadimedja, Holyness N (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Safety and comfort of the work environment is one of the things that each worker is entitled to in a scope of work. This right is based on labor laws and regulations which stipulate that the welfare and safety of workers is one of the main priorities that must be provided by employers as employers. All efforts in providing work safety should be optimized, especially the management system within the company and the role of existing supervision. The Occupational Safety and Health Management System (SMK3) is one of the platforms created to anticipate work accidents within the company. However, the system will not run optimally without systematic supervision, one of which is from labor inspectors. For this reason, it is necessary to know more about the role of labor inspectors in implementation of SMK3 by the company in order to prevent work accidents for workers.